The Moderating Effect Of Enterprise Risk Management On The Relationship Between Audit Committee Characteristics And Corporate Performance: A Conceptual Case of Jordan - Saddam Shatnawi; Mustafa Mohd Hanefah; Abdelhakhem Adaa; Monther Eldaia (Human Resource Management Academic Research Society, 2024)
Indexed by ERA